Pattern-based Histologic Approach in Very Early Onset IBD: Main Features and Differential Diagnosis. (March 2022) - Parente, Paola; Mastracci, Luca; Vanoli, Alessandro; Fassan, Matteo; Pastore, Maria; Bossa, Fabrizio; Francalanci, Paola; Alaggio, Rita; Graziano, Paolo; Grillo, Federica
Abstract : Very early onset inflammatory bowel disease (VEO-IBD) is a clinical umbrella classification composed of IBD-like diseases encompassing both classic IBD (Crohn's disease and ulcerative colitis) and monogenic disorder, both arising before 6 years of age. VEO-IBD patients present significant clinical differences from IBD occurring in older children and in adults, including more severe disease, often unresponsive to conventional IBD therapy and a greater proportion of cases featuring an underlying genetic alteration. Histologic findings of gastrointestinal biopsies can show an IBD-like pattern (both Crohn's disease-like and ulcerative colitis-like pattern), an apoptotic-like and enterocolitis-like pattern. Findings of specific morphologic alterations, such as villous blunting, apoptosis, dense eosinophilic infiltrates, lack of plasma cells and severe glandular atrophy, can suggest a monogenic disorder. Moreover, individuals with monogenic disorders may develop significant problems such as primary immunodeficiency, impacting treatment options. Finally, IBD histology in childhood can differ from that in older patients and adults. This complexity makes a differential diagnosis between IBD and other pediatric diseases involving the gastrointestinal tract difficult, especially considering that histologic features can be similar between different diseases. Without an appropriate diagnosis, the clinical course of VEO-IBD has greater potential for escalated treatment regimens involving extensive surgery and more intensive medical therapies rather than specific therapy directed toward the underlying defect. For these reasons, a pattern-based histologic approach correlated with clinical and laboratory findings with a multidisciplinary approach is fundamental to reach a correct diagnosis in an adequate clinical context.